The Call for Islamic Economics: Shades of Contestation - Ibrahim, Azhar (Shirkah: Journal of Economics and Business, 2017)
This paper attempts to highlight some of the criticisms made against the ideas of Islamic economics. The discourse of Islamic economics is relatively recent, although its expression could be traced to more than five decades ago. Today there are countless discussions and affirmations for Islamic economics, coming from both experts in the area of economy and Islamic legal thought, apart from the many journalistic advocacy type that is enamored by the call for the establishment of Islamic economics, or at least the Islamic banking. While there is much celebration to this idea, the criticism against it is far less and hardly noticeable. To date, Timur Kuran and to some extent Nazih Ayubi have been vocal in highlighting the rhetorics and the insubstantiality of the idea of Islamic economics.Keywords: Islamic economics, Islamic identity, sharia